Mass measurements of Ga60-63 reduce x-ray burst model uncertainties and extend the evaluated T=1 isobaric multiplet mass equation - Paul, Stefan Felix; Bergmann, J.; Cardona, J. D.; Dietrich, Kilian; Dunling, E.; Hockenbery, Z.; Hornung, C.; Izzo, C.; Jacobs, A.; Javaji, A.; Kootte, B.; Lan, Y.; et al. (Physical review, 2021)
We report precision mass measurements of neutron-deficient gallium isotopes approaching the proton drip line. The measurements of 60-63Ga performed with the TITAN multiple-reflection time-of-flight mass spectrometer provide a more than threefold improvement over the current literature mass uncertainty of 61Ga and mark the first direct mass measurement of 60Ga. The improved precision of the 61Ga mass has important implications for the astrophysical rp process, as it constrains essential reaction Q values near the 60Zn waiting point. Based on calculations with a one-zone model, we demonstrate the impact of the improved mass data on prediction uncertainties of x-ray burst models. The first-time measurement of the 60Ga ground-state mass establishes the proton-bound nature of this nuclide, thus constraining the location of the proton drip line along this isotopic chain. Including the measured mass of 60Ga further enables us to extend the evaluated T=1 isobaric multiplet mass equation up to A=60.0